Minskad snölast och ökad solelproduktion i arktiskt klimat - Johansson, Gustav (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2024)
This project investigated the feasibility of installing photovoltaic systems with electrical heating on underdimensioned roofs in arctic climate, with the purpose of reducing the snow load. The northern part of Sweden is undergoing an industrial transition and more renewable electricityneeds to be produced. Solar panels on roofs can offer short processes from planning to production of renewable energy, reduced load on the electricity grid and more energy-efficient buildings, without interfering with other interests. Experimental tests were conducted on a snow-covered solar panel mounted on load cells while electric heating was supplied. The snow load was measured during the test, which was conducted twice. During the first test the temperature of the air was −3℃ and an average load reduction of 17N/(m2,h) was observed. The second test was performed at an air temperature of −11℃, and an average load reduction of 9N/(m2,h) was observed. The efficiencies were 40% for the first, and 22% for the second test. The project also included a case study on a building that was underdimensioned for the snow load and thus in need of manual snow removal. It was considered whether a PV system with electric heating for snow removal would be a valid option technically and economically. Two PV-systems were designed in the case study. One system was designed to make manual snow removal accessible, and the other system was equipped with electric heating to reduce snow load. Based on the experimental tests it was concluded that snow load reduction could be performed quick enough, making the technology feasible if precipitation can be predicted in advance. The system designed for manual snow removal resulted in an energy production of 174.5MWh with ????tot=244.8kW, ????????????=333 000SEK and ????????????=7.8%. The system with electric heating resulted in an energy production of 266.6MWh with ????tot=374kWp. The reason why the system with electrical heating generates more energy is because the whole roof area was covered with solar panels. Same percentage of ...